2019
DOI: 10.5937/ijcrsee1901051m
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style in the context of the conflict between parental and business roles

Abstract: The paper discusses the connection between parenting style and the scope of the conflict between parental and business roles. For a parenting style, we used the concept of Dianne Baumrind (1966/2002), who defined three basic types of a parent-child relationship: authoritarian, authoritative and permissive. The problem of conflict is accessed through the theory of work-family conflict, the Greenhaus and Beutell model (Greenhaus and Beutell, 1985), according to which the impact of work on a family consists of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…Specifically, higher WFC levels showed a negative association with the authoritative parenting style and a positive association with the authoritarian or permissive parenting style. These findings are consistent with the result of Matejević and Đorđević [ 21 ]. Maternal WFC might hurt the quality of parenting within the family system due to occupational exhaustion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, higher WFC levels showed a negative association with the authoritative parenting style and a positive association with the authoritarian or permissive parenting style. These findings are consistent with the result of Matejević and Đorđević [ 21 ]. Maternal WFC might hurt the quality of parenting within the family system due to occupational exhaustion.…”
Section: Discussionsupporting
confidence: 93%
“…They made most decisions about their children’s activities, leaving little room for their opinions, more so than Korean American working mothers [ 20 ]. Permissive parenting style is characterized by parenting behavior with little or no rules or restrictions on the child, and low levels of control [ 19 , 21 ]. A study reported that a higher level of WFC was associated with the permissive or authoritative parenting style, and a lower level of WFC was associated with the authoritative parenting style [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ninety seven percent of the research participants agree with this statement. This assumption is in accordance with recent research that links (long-term) exclusion of children from family life with long-term adverse outcomes, especially socioemotional difficulties (Vendell et al, 2010), and economically disadvantaged family status with dysfunctional parents and poorer achievements of children (Matejević and Đorđević, 2019;Zygmunt-Fillwalk, 2011).…”
Section: Parentingsupporting
confidence: 89%
“…Previous studies showed that parents who experience more W→F-conflict and F→W-conflict show more negative parenting such as an authoritarian parenting style (Matejević & Đorđević, 2019), hostile parenting behavior (Cooklin et al, 2015(Cooklin et al, , 2016 and negative communication (such as yelling to the child) (Eynde et al, 2000), less positive parenting such as less parental consistency and warmth (Cooklin et al, 2015(Cooklin et al, , 2016 and more negative feelings towards the child (Cooklin et al, 2015(Cooklin et al, , 2016 and lower perceived relationship quality (Vieira et al, 2016). In this study, we examined three different aspects of perceived parenting, namely positive encouragement, coercive discipline, and the parent-child relationship.…”
Section: The Associations Between F→w-conflict and W→f-conflict With mentioning
confidence: 99%
“…The second aim of the current study was to investigate associations between W→Fconflict/F→W-conflict with perceived parenting (positive encouragement, coercive parenting and parent-child relationship), and scrutinize whether and to what extent these associations became stronger during the Covid-19 lockdown. Previous studies showed that parents who experience more conflict between work and family, demonstrated lower quality of parenting behavior (Cooklin et al, 2016;Matejević & Đorđević, 2019). During the lockdown period, associations between conflict and perceived parenting might have been stronger given the fact that parents were expected to be intensively involved with their children's care and school work, while at the same time they could rely less on others for support with childcare (Prime et al, 2020), which increases the likelihood that conflict spills over to perceived parenting.…”
Section: Introductionmentioning
confidence: 99%